Revitalising psychiatry: Stevens, A and Price, J (1996) Evolutionary psychiatry. London: Routledge. ISBN 0-415-13840-X pbk. xi+267 pages - Henzi, Peter (PINS-Psychology in Society, 2026)
The central tenet of this book is that psychiatry will be revitalised, and will assume its place within a new science of humanity, by application of the understanding that there is, importantly, an evolved component to expressed human nature. This stance, which might once have attracted strong opprobrium from the psychiatric community for its acknowledgement of biology, is now comfortably situated within the increasingly established domain of evolutionary psychology and is, more immediately, an explicit extension of the ideas of Randolph Nesse and George Williams. Nesse and Williams, the latter a distinguished evolutionist in his own right, have established a field of enquiry they call Darwinian medicine (see Evolution and healing: The new science of Darwinian medicine, Orion Press, 1996) and which is an attempt to find evolutionary explanations for vulnerabilities to disease in order to better direct treatment. If the human body is selected to perform efficiently within a particular environment, then we might expect problems to manifest themselves once the environment is sufficiently altered. Since the basic features of the human body and, more controversially, the human mind are held to reflect selection pressures operating during the paleolithic, it is not surprising that the extraordinary changes in human lifestyle contingent on the emergence of agriculture ten thousand years ago have had far-reaching consequences for us. We have a physiological craving for sugar, fat and salt, for example, because these are very valuable but scarce components of the standard hunter-gatherer diet. The undesirable corollary, in times of plenty, is the epidemic of obesity with all its attendant health problems, that plagues the developed world and fuels a colossal fast food industry. Ironically, even the generally improved health of most modem populations reveals the constraints of our past. The degenerative muscle disease, Huntingdon’s Chorea, is due to the action of a late expressing gene. It doesn’t manifest itself prior to the age of forty, by which time its original carriers would have been post-reproductive if not dead. Since it could therefore not have been selected against by the improved reproductive success of non-carriers, it survives to haunt us in these times of greatly increased longevity.